5-Substituted 1H-tetrazoles as effective corrosion inhibitors for mild steel in 1 M hydrochloric acid. Issue 5 (1st September 2016) - Verma, Chandrabhan; Quraishi, M.A.; Singh, A.
Abstract: The corrosion inhibition efficiency of ( E )-3-phenyl-2-(1H-tetrazole-5-yl)acrylonitrile (PTA), ( E )-3-(4-nitrophenyl)-2-(1H-tetrazole-5-yl)acrylonitrile (NTA), and ( E )-3-(4-hydroxyphenyl)-2-(1H-tetrazole-5-yl)acrylonitrile (HTA) on mild steel in 1 M HCl was tested using experimental and theoretical methods. The results show that the inhibition efficiency increases with the increasing concentration, and maximum values were obtained at a 40 mg L −1 concentration. The inhibition efficiency of the studied inhibitors follows the order HTA (98.69%) > NTA (96.60%) > PTA (93.99%). Polarization studies suggest that the tetrazoles behave as cathodic inhibitors. The adsorption of the tetrazoles on the mild steel surface obeys the Langmuir adsorption isotherm. In the present study, the values of the free energy of adsorption ( − Δ G ads 0 ) vary from 34.92 to 39.71 kJ mol −1 . The adsorption of the tetrazoles on the mild steel surface is supported by SEM, EDX and AFM studies. Quantum chemical calculations provide good support to the experimental results.